Statistical mechanics - Pathria, R. K., 1933 (Elsevier, 1996)
This text is designed for postgraduate courses in statistical mechanics, and provides a basic grounding in a manner that brings out the essence of the subject with due rigour but without undue pain. This classic text, which was first published in 1972 and has continued to be popular ever since, has now been brought up to date by incorporating the remarkable developments in the field of phase transitions and critical phenomena that have taken place in the intervening years. This has been done by adding three new chapters which will enhance the usefulness of this book both for students and instructors. Widely acclaimed for its clean derivations and clear explanations, Statistical Mechanics in its second edition will continue to provide further generations of students with a solid training in the methods of statistical physics.